PENGEMBANGAN PRODUK MESIN PENGERING DAUN TEH BERBASIS TUBULAR HEATER - Imron Rosyadi (2021)
Tea is a very crucial commodity in public consumption in Indonesia, the development of industrial-scale factories in processing tea leaf drying in the regions is still considered traditional and damaging to the environment, such as drying equipment that still uses firewood, innovation and development of fast, efficient, economical and friendly solutions. the environment in the tea drying process becomes a material that needs to be discussed in this discussion in a prototype to produce good and cheap process uses, which is a challenge in its development. In order to produce the optimal drying temperature for tea at 60°-80° C, this tool is very effective because it can maintain a stable temperature. Tubular Heater-based tea leaf drying machines and electric motors are one of the developments that can be used as alternatives as materials that are environmentally friendly, economical, and efficient. The working principle of this tool is the same as an oven, this tool can be used on all types of tea plants, can be scaled up for industry and is still categorized as an economical and environmentally friendly tool, partitions that are easy to find and practicality in use are important for sales can compete in the market in production.